2016
DOI: 10.1021/jacs.5b13279
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Density Functional Theory Modeling of Li Binding: Thermodynamics and Redox Properties of Quinone Derivatives for Lithium-Ion Batteries

Abstract: The Li-binding thermodynamics and redox potentials of seven different quinone derivatives are investigated to determine their suitability as positive electrode materials for lithium-ion batteries. First, using density functional theory (DFT) calculations on the interactions between the quinone derivatives and Li atoms, we find that the Li atoms primarily bind with the carbonyl groups in the test molecules. Next, we observed that the redox properties of the quinone derivatives can be tuned in the desired direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
225
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(248 citation statements)
references
References 49 publications
23
225
0
Order By: Relevance
“…It was shown in several studies that the energies of the LUMO significantly correlate to the voltage achieved with materials operating by reduction as the electron from the attached alkali atom, e.g., Li, will occupy the LUMO of the molecule (Burkhardt et al, 2013;Liang et al, 2013;Kim et al, 2015bKim et al, , 2016Lüder et al, 2017a). Specifically, a stabilization of the LUMO energy of comparable systems, for instance by substitutional doping, show strong correlations to voltage increase.…”
Section: Limits Of Electronic Effects For Voltage Increase In Organicmentioning
confidence: 99%
“…It was shown in several studies that the energies of the LUMO significantly correlate to the voltage achieved with materials operating by reduction as the electron from the attached alkali atom, e.g., Li, will occupy the LUMO of the molecule (Burkhardt et al, 2013;Liang et al, 2013;Kim et al, 2015bKim et al, , 2016Lüder et al, 2017a). Specifically, a stabilization of the LUMO energy of comparable systems, for instance by substitutional doping, show strong correlations to voltage increase.…”
Section: Limits Of Electronic Effects For Voltage Increase In Organicmentioning
confidence: 99%
“…[13] Janga nd co-workers found that the redoxp roperties of the AQ derivativesc an be improved by modifying their chemical structures with electron-withdrawing carboxylg roups. [12] Systemic theoretical calculations were carriedo ut to compare the electrochemical performance of the PQ derivatives modified by heterocycle substitution( series At oD )a nd by functional-group incorporation.T he first and second lithiation potentials, average reduction potentials, theoretical capacities, and energy densities of 40 PQ derivatives are computed (see Ta ble S1 in the Supporting Information). Molecules with the best redox properties are selected and compared with PQ as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Jang and co-workers studied the Li-binding thermodynamics and redox potentialso ff unctionalized anthraquinone (AQ) derivatives. [12] They found that the redox properties of the AQ derivatives can be improved by modifying their chemical structures with electron-withdrawingc arboxyl groups. These studies highlight the potential for carbonyl compounds to be improvedt hrough the use of electron-withdrawingf unctionalgroup substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, density functional theory investigations demonstrated an enhancement of the initial lithium ion intercalation potential due to concerted reactions between multiple oxygen centers and lithium ions. [45] Although increasing the size of the aromatic structure decreases the solubility in usual organic electrolytes and can yield large theoretical capacities, upon reduction, electrostatic repulsions could be imposed by the sterically hindered and close redox groups limiting the specific capacity. In addition, this may mix up the crystal packing resulting in dissolution in the liquid electrolyte and capacity fading.…”
Section: Quinones Based π-Conjugated Active Materialsmentioning
confidence: 99%